The metonymic mechanism of English translation of Chinese intangible cultural heritage terms from the perspective of cognitive psychology - Jiang, Liping; Al-Shaibani, Ghayth K. Sh.; Yang, Fenglin; Cheng, Mengmeng; Huang, Minghuan (Frontiers in Psychology, 2022)
The translation of Intangible Cultural Heritage (ICH) terms is an important practical aspect of cross-lingual expressions related to ICH knowledge. Chinese ICH terms are heavily loaded with specific historical and cultural knowledge and regional characteristics. Based on cognitive psychology, this paper analyzes the metonymic mechanism of traditional translation techniques such as substitution in the English translation of Chinese ICH terms. The English translation of Chinese ICH nominal terms can be realized based on the metonymic mechanism of replacing either a superordinate with a subordinate of the linguistic structure or a subordinate of the linguistic structure with a subordinate of the linguistic structure in the pair language, English-Chinese. The English translation of Chinese ICH verbal terms can regard the whole verbal action as an event process and can highlight one aspect of the process through a metonymic mechanism as well. This paper holds that metonymy is an important psychological motivation and cognitive mechanism for translation skills such as substitution as it brings the relationship between the corresponding items of the target language and the source language into a unified interpretation framework. Hence, this may add some significance to the research of translation theory and translation practice. This also contributes to the UN Sustainable Development Goal number 17 which seeks global parternship for sustainable development.